2020
DOI: 10.1287/isre.2019.0918
|View full text |Cite
|
Sign up to set email alerts
|

When Loyalty Goes Mobile: Effects of Mobile Loyalty Apps on Purchase, Redemption, and Competition

Abstract: This research investigates how a shift from traditional loyalty cards to mobile-driven loyalty apps affects consumers’ reward redemption patterns, purchase behaviors, and store-level competition. The findings indicate that loyalty app adoption is associated with increased expenditure and purchase frequency as well as more active point redemption. In a multivendor loyalty program (MVLP) context, the use of loyalty apps is associated with spillover effects in which case customers visit more stores that they had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…WOM has been shown to create brand communities within music fans (Cova et al., 2021). eWOM can be linked by electronic loyalty programs (eg via apps), and those who use loyalty apps are more vulnerable to accepting deals (Son et al., 2020, p.835) which BO can deploy to retain existing customers, and attract new ones. Furthermore, previous research finds that virtual interactivity is a driver of brand involvement (Elsharnouby et al., 2021).…”
Section: Discussion: Resonance At the Operamentioning
confidence: 99%
“…WOM has been shown to create brand communities within music fans (Cova et al., 2021). eWOM can be linked by electronic loyalty programs (eg via apps), and those who use loyalty apps are more vulnerable to accepting deals (Son et al., 2020, p.835) which BO can deploy to retain existing customers, and attract new ones. Furthermore, previous research finds that virtual interactivity is a driver of brand involvement (Elsharnouby et al., 2021).…”
Section: Discussion: Resonance At the Operamentioning
confidence: 99%
“…At the intersection with customer loyalty, Heim and Sinha (2001) study electronic food retailers and show that ease of website navigation, more detailed product information, cheaper prices, higher product availability, timeliness of delivery, and ease of return increase customer loyalty. Leveraging data on a multi‐vendor loyalty program, Son et al (2020) show that adoption of loyalty apps may lead to deal‐susceptible behavior (i.e., selectively buying highly discounted products). Özer et al (2020) estimate the customers' stock‐out and high‐price regrets using customer clickstream data of a fashion retailer and show that more frequent website visitors have more stock‐out (and less high‐price) regret.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been shown that loyalty customers are more knowledgeable about product offerings (Reinartz & Kumar, 2002) and tend to be more vulnerable to deals (Son et al, 2020). In addition, it is well documented that these customers act strategic to earn rewards, attain status, or move to a higher tier (Kivetz et al, 2006; Orhun et al, 2022).…”
Section: Contextual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesquisas futuras poderiam avaliar a influência da frequência de uso em variáveis antecedentes à confiança e a satisfação como a reputação do aplicativo e da empresa, e a influência da falha e da recuperação da falha na prestação de serviço na relação entre a lealdade online e seus antecedentes. Son et al (2020), por exemplo, testaram o efeito da transição de programas de fidelidade de compras off-line para uso de aplicativos online e identificaram que, a despeito do incremento de uso dos programas, a facilidade e grande variedade dos clientes os leva ao comportamento transacional -de busca de ofertas relâmpago com preços agressivos -levando ao oposto do esperado, o comportamento relacional. Nesse sentido, vale investigar como a interação entre a reputação, as falhas e recuperações de falhas e a frequência de uso opera nos diferentes formatos de programas de fidelidade on e off-line.…”
Section: R C Aunclassified